Clinical features of actinomycosis: A retrospective, multicenter study of 28 cases of miscellaneous presentations. Issue 24 (June 2016) - Bonnefond, Simon; Catroux, Mélanie; Melenotte, Cléa; Karkowski, Ludovic; Rolland, Ludivine; Trouillier, Sébastien; Raffray, Loic
Abstract : Abstract: Actinomycosis is a rare heterogeneous anaerobic infection with misleading clinical presentations that delay diagnosis. A significant number of misdiagnosed cases have been reported in specific localizations, but studies including various forms of actinomycosis have rarely been published. We performed a multicenter retrospective chart review of laboratory-confirmed actinomycosis cases from January 2000 until January 2014. We described clinical characteristics, diagnostic procedures, differential diagnosis, and management of actinomycosis of clinical significance. Twenty-eight patients were included from 6 hospitals in France. Disease was diagnosed predominately in the abdomen/pelvis (n = 9), orocervicofacial (n = 5), cardiothoracic (n = 5), skeletal (n = 3), hematogenous (n = 3), soft tissue (n = 2), and intracranially (n = 1). Four patients (14%) were immunocompromised. In most cases (92 %), the diagnosis of actinomycosis was not suspected on admission, as clinical features were not specific. Diagnosis was obtained from either microbiology (50%, n = 14) or histopathology (42%, n = 12), or from both methods (7%, n = 2). Surgical biopsy was needed for definite diagnosis in 71% of cases (n = 20). Coinfection was found in 13 patients (46%), among which 3 patients were diagnosed from histologic criteria only. Two-thirds of patients were treated with amoxicillin. Median duration of antibiotics was 120 days (interquartile range 60–180), whereas the median follow-up time was 12 months (interquartile range 5.25–18). Two patients died. This study highlights the distinct and miscellaneous patterns of actinomycosis to prompt accurate diagnosis and earlier treatments, thus improving the outcome. Surgical biopsy should be performed when possible while raising histologist's and microbiologist's awareness of possible actinomycosis to enhance the chance of diagnosis and use specific molecular methods.